PROBLEMS OF AIRPLANE UNSTEADY AERODYNAMICS - Udartsev, E.P. (Proceedings of National Aviation University (archive), 2005)
Consider the question about influence of unsteady flight on the size of drag and lift coefficients. This influence can changes the trajectory of flight and important in case flight in turbulent atmosphere. Distinctive features of this investigation are obtaining data about aerodynamic drag changing aerodynamic in process unsteady flight. This question is not consider in many articles about influence unsteady forces on dynamic of flight plane.